Semiconducting Open‐Shell Radicals for Precise Tumor Activatable Phototheranostics - Jie Zhang; Haifen Luo; Wen Ma; Jingqi Lv; Bo Wang; Fengwei Sun; Weijie Chi; Zhuting Fang; Zhen Yang (Advanced Science)
Abstract Semiconducting open‐shell radicals (SORs) have promising potential for the development of phototheranostic agents, enabling tumor bioimaging and boosting tumorous reactive oxygen species (ROS). Herein, a new class of semiconducting perylene diimide (PDI), designated as PDI(Br)n with various numbers of bromine (Br) atoms modified on PDI's bay/ortho positions is reported. PDI(Br)n is demonstrated to transform into a radical anion, [PDI(Br)n]•−, in a reducing solution, with a typical g‐value of 2.0022. Specifically, [PDI(Br)4/6]•− is generated in the weakly reductive tumor‐mimicking solution and exhibits high stability in air. Quantum chemical kinetic simulation and ultrafast femtosecond transient absorption spectroscopy indicate that [PDI(Br)6]•− has a low π–π stacking energy (0.35 eV), a fast electron transfer rate (192.4 ps) and energy gap of PDI(Br)6 (ΔES1, T1 = 1.307 eV, ΔES1, T2 = 0.324 eV) respectively, which together result in excited‐state charge transfer characters. The PDI(Br)6 nanoparticle radicals, [PDI(Br)6] NPs•−, specifically enable chemodynamic and type‐I photodynamic ROS generation in tumors, including superoxide and hydroxyl radicals, which elicit immunogenic cell death effect. Also, [PDI(Br)6] NPs•− facilitate activatable bioimaging‐guided therapy due to their photoacoustic signal at 808 nm and NIR‐II emission at 1115 nm. The work paves the way for the design of SORs for precise cancer theranostics.